Perception and pain thresholds for cutaneous heat and cold, and rectal distension: associations and disassociations. Issue 12 (12th August 2013) - Horing, B.; Kugel, H.; Brenner, V.; Zipfel, S.; Enck, P.
Abstract Background Hypersensitivity to somatic or visceral pain has been reported in numerous clinical conditions such as fibromyalgia or the irritable bowel syndrome, and general hypersensitivity has been proposed to be the underlying mechanism. However, cross‐modal relationships especially between somatic and visceral pain have rarely been investigated even in healthy volunteers. Furthermore, psychological influences on pain have rarely been characterized across modalities. Methods Sixty‐one healthy participants underwent testing of perception and pain thresholds for cutaneous thermode heat and cold, as well as for rectal balloon distension. Psychological testing for anxiety, depression, and pain experience (including catastrophizing and coping) as well as cardiac interoception was performed. Measurement quality and the correlations between the different modalities were examined. Key Results Significant correlations existed between the perception thresholds for cold/heat (τB = −0.28, p = 0.002) and cold/distension (τB = −0.21, p = 0.03) and for the pain thresholds for cold/heat (r = −0.61, p < 0.001) and heat/distension (r = 0.33, p = 0.01). No association was found between pain thresholds and anxiety, depression, psychological experience with and processing of pain, or cardiac interoception. Retest reliabilities for pain measurements were satisfying after short intertrial intervals (all intraclass correlation coefficients >0.8), but less so after longer intervals. The individuals contributing to the respective correlations differ between measurements. Conclusions & inferences Moderate associations were found for pain thresholds across modalities. The strength of the associations and their stability over time warrants further investigation and might serve to increase the understanding of conditions affecting multiple pain modalities.